2019
DOI: 10.1016/j.nepr.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of community of inquiry framework to online nursing education: A cross-sectional study

Abstract: The Community of Inquiry (CoI) framework has the potential to contribute to online education by addressing the nexus of pedagogy, technology, and learners' needs. However, there has been limited investigation of the application of CoI to Australian online tertiary education, with the awareness of CoI amongst Australian nurse educators being unknown. This paper reports on a project which used an online survey to investigate the level of awareness of the CoI framework and its applicability to the design of onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Blended learning has the ability to initiate a plethora of discussions since it promotes communication via online group chat for dialogues and debates (Garrison & Kanuka, 2004). The three elements of presence (social, teaching and cognitive) in this study suggested that the blended learning design was successful and the results were consistent with other studies which reported receiving the highest mean teaching score for presence and lowest score for social presence (Nagel, 2012; Smadi et al, 2019). The lowest mean score for social presence implied that students were still uncomfortable with learning and interacting online.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Blended learning has the ability to initiate a plethora of discussions since it promotes communication via online group chat for dialogues and debates (Garrison & Kanuka, 2004). The three elements of presence (social, teaching and cognitive) in this study suggested that the blended learning design was successful and the results were consistent with other studies which reported receiving the highest mean teaching score for presence and lowest score for social presence (Nagel, 2012; Smadi et al, 2019). The lowest mean score for social presence implied that students were still uncomfortable with learning and interacting online.…”
Section: Discussionsupporting
confidence: 91%
“…Despite its apparent effectiveness in various disciplines, the use of CoI framework is not common in nursing and health sciences education (McCutcheon et al, 2014; Mills et al, 2016; Phillips et al, 2013). Studies conducted within the nursing context also received low response rates and had small sample sizes (Mills et al, 2016; Smadi et al, 2019). Given the limited studies focusing on the implementation of CoI framework in biomedical‐related education discipline, its potential to enrich nurse education warrants further examination.…”
Section: Introductionmentioning
confidence: 99%
“…In designing for learning, the interviewees commented on the importance of creating an emotionally safe place for students where they could be challenged and yet feel able to engage and collaborate with each other (social design). The literature highlights the importance of teacher presence and the positive effect on learner’s perceptions (Männistö et al 2019 ; Smadi et al 2019 ). This was evident in one of the courses which presents historical and recent colonisation experiences within Aotearoa New Zealand and invites students to learn about, consider, and challenge their perceptions of history, their place in it, and the ongoing effects of colonisation (epistemic design).…”
Section: Emerging Themesmentioning
confidence: 99%
“…To our knowledge, the CoI framework has shown potential contributions in learning satisfaction and higher‐order learning. It was widely introduced into a series of disciplines, such as health sciences (Moser et al., 2015 ), business (Chen et al., 2017 ) and languages (Sun et al., 2017 ), while limited research related to online learning in nursing education (Smadi et al., 2019 ). A concern exists in that nursing programmes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A concern exists in that nursing programmes (e.g. SPD module) require advanced communication skills (Lewis, 2012 ), although the CoI framework is currently mainly implemented in online environments, such distancing and virtual nature of the programme may hinder the development of these skills (Smadi et al., 2019 ). Another concern related to the online environment is that medical or nursing undergraduate education is mostly face‐to‐face or blended due to characteristics of the health sciences.…”
Section: Introductionmentioning
confidence: 99%